1978
DOI: 10.1530/acta.0.0880428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cimetidine on Prolactin, Lh, and Sex Steroid Secretion in Male and Female Volunteers

Abstract: The histamine H2-receptor antagonist cimetidine, which has recently been introduced for the treatment of gastric and duodenal ulcers and haemorrhage, respectively, stimulates prolactin (PRL) secretion. The release of PRL after a bolus injection of the compound is significantly higher in female than in male volunteers, and is more pronounced during the luteal than during the follicular phase of the menstrual cycle. Oral administration of the drug stimulates PRL to a similar extent as parenteral administration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…We have previously reported (Carlson & Ippoliti, 1977) and others have confirmed (Bohnet et al, 1978;Daubresse et al, 1978) that i.v. In man, evidence is strongest for a PRL-regulating role.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We have previously reported (Carlson & Ippoliti, 1977) and others have confirmed (Bohnet et al, 1978;Daubresse et al, 1978) that i.v. In man, evidence is strongest for a PRL-regulating role.…”
Section: Discussionsupporting
confidence: 75%
“…Experiments in animals and man have suggested that histamine may be an important regulator of pituitary hormone secretion. In addition to the demonstration of substantial concentrations of histamine and a histamine-sensitive adenylate cyclase in the hypothalamus (Kizer et al, 1976;Sat0 et al, 1974;Hegstrand et al, 1976), the administration of histamine or its antagonists has been reported to alter pituitary hormone release in rats (Libertun & McCann, 1976;Donoso et al, 1976;Arakelian & Libertun, 1977) and man (Carlson & Ippoliti, 1977;Pontiroli & Pozza, 1978;Bohnet et al, 1978;Pontiroli et al, 1976). The present studies were undertaken to explore further the role of histamine in the modulation of human pituitary function.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Our experiments showed that acute intra venous administration of cimetidine did not change the basal levels of the hormones exam ined and this is in accordance with data re ported by other authors (3,20). Apart from a non-significant increase in hTSH in response to TRH which suggests a further, more thorough investigation in a greater number of subjects to be performed, the only significant change was the increase in prolactin in response to TRH during the infusion of cimetidine.…”
Section: Discussionsupporting
confidence: 94%
“…This response is more pro nounced in women than in men [2] and is dose-related [4]. In addition, we have shown that intravenous infusion of this drug also increases the prolac tin response to exogenous thyrotropin-releasing hormone (TRH) [17].…”
Section: Introductionmentioning
confidence: 95%